Chronic treatment with the anti-diabetic drug metformin rescues impaired brain mitochondrial activity and selectively ameliorates defective cognitive flexibility in a female mouse model of Rett syndrome. (15th February 2023) - Urbinati, Chiara; Lanzillotta, Chiara; Cosentino, Livia; Valenti, Daniela; Quattrini, Maria Cristina; Di Crescenzo, Livia; Prestia, Francesca; Pietraforte, Donatella; Perluigi, Marzia; Di Domenico, Fabio; Vacca, Rosa Anna; De Filippis, Bianca
ABSTRACT: Metformin is the most common anti-diabetic drug and a promising therapy for disorders beyond diabetes, including Rett syndrome (RTT), a rare neurologic disease characterized by severe intellectual disability. A 10-day-long treatment rescued aberrant mitochondrial activity and restrained oxidative stress in a female RTT mouse model. However, this treatment regimen did not improve the phenotype of RTT mice. In the present study, we demonstrate that a 4-month-long treatment with metformin (150 mg/Kg/day, delivered in drinking bottles) provides a selective normalization of cognitive flexibility defects in RTT female mice at an advanced stage of disease, but it does not affect their impaired general health status and abnormal motor skills. The 4-month-long treatment also rescues the reduced activity of mitochondrial respiratory chain complex activities, the defective brain ATP production and levels as well as the increased production of reactive oxidizing species in the whole blood of RTT mice. A significant boost of PGC-1α-dependent pathways related to mitochondrial biogenesis and antioxidant defense occurs in the brain of RTT mice that received the metformin treatment. Further studies will have to verify whether these effects may underlie its long-lasting beneficial effects on brain energy metabolism. Highlights: Metformin normalizes flexible responses for new external cues in Rett syndrome mice. A rescue of Rett brain mitochondrial defects persists after chronic Met treatment. Oxidative imbalance is restored after chronic Met treatment in Rett mouse blood. Modulation of PGC-1α dependent pathways may explain Met beneficial effects for Rett.